Pain Control by Targeting Oxidized Phospholipids: Functions, Mechanisms, Perspectives - Oehler, Beatrice; Brack, Alexander; Blum, Robert; Rittner, Heike L. (Frontiers in Endocrinology, 2021)
Within the lipidome oxidized phospholipids (OxPL) form a class of chemically highly reactive metabolites. OxPL are acutely produced in inflamed tissue and act as endogenous, pain-inducing metabolites. They excite sensory, nociceptive neurons by activating transient receptor potential ion channels, specifically TRPA1 and TRPV1. Under inflammatory conditions, OxPL-mediated receptor potentials even potentiate the action potential firing rate of nociceptors. Targeting OxPL with D-4F peptide or antibodies like E06 can be used to control acute, inflammatory pain syndromes. The basics of how OxPL operate as agonists and excitants are not completely understood: Due to the difficulties to stabilize and measure these highly reactive metabolites in a physiological context, it is not yet clear, how OxPL contribute to the many functions of the epilipidome in vivo. With a focus on proalgesic specificities of OxPL, this article discusses, how targeting defined substances of the lipidome can contribute to mechanism-based therapies against primary and secondary chronic inflammatory or possibly also neuropathic pain.